Pengembangan Modul Tata Rias Wajah pada Program Beauty Class Reporter Narasi TV - Alifia Sani Husen; Nurul Hidayah; Aniesa Puspa Arum (Mathematics Education Study Program, 2025)
This research was developed through the lack of learning media used in the beauty class program specifically for reporters held on a television station, especially Narasi TV. This study aims to develop a make-up module in a beauty class aimed at TV station reporters. Television reporters need appropriate make-up skills to support a professional appearance through outdoor broadcasts and in the studio. This module is designed to meet these needs by providing systematic, easy-to-understand guidance that is in accordance with professional beauty standards. The research method used is Research and Development (R&D) with a 4D development model (define, design, develop, disseminate). The data collection technique uses a questionnaire distribution in the form of a questionnaire with qualitative and quantitative data analysis techniques. The results of the study showed that the feasibility value obtained by media experts was 100% and the results of the material expert validity test were carried out in 2 stages with a final value of 87%. Meanwhile, in the trial, students received a one-to-one assessment of 88.6% and in small groups of 88.4%. Based on the data obtained, it can be concluded that the Makeup module in the Narasi TV Beauty Class Reporter is said to be